Effective Classroom Management as a Quick Solution to Improve Student Participation and Motivation in the Learning Process - Abidin, Zaenal; Muhammad, Norhazlin (Zabags International Journal of Education, 2024)
This study aims to evaluate the effectiveness of classroom management in increasing student participation and motivation at MI Darul Akhlak, Tanjung Jabung Timur Regency. The research method used is a qualitative descriptive approach with data collection techniques in the form of observation, interviews, and documentation. This study observes how the implementation of good classroom management can create a conducive learning environment and encourage students to be more active in learning. The results of the study indicate that effective classroom management, including careful planning, flexible seating arrangements, the use of relevant learning media, and positive interactions between teachers and students, can increase student focus and involvement in the learning process. Some obstacles in the implementation of classroom management include low student awareness of learning responsibilities and the existence of disruptive extracurricular activities. In conclusion, good classroom management plays an important role in creating a conducive learning atmosphere and increasing student motivation. It is recommended that teachers maximize classroom management strategies and involve students in the learning process. Students are also expected to be able to increase awareness of the importance of active participation in teaching and learning activities.